The Building Sustainable Performance of the Umrah Travel Business in DKI Jakarta: Studies on Umrah Travel in DKI Jakarta Province - Murdani; Sri Widyastuti; Widarto Rachbini (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study examines the effect of Quality Management and ethical leadership on the sustainability of the Umrah Travel business through corporate performance. A structured questionnaire was used to collect data from managers of Umrah Travel who work for the companies surveyed. Data from random sampling by distributed questionnaires to 80 participants found 395 official Umroh travels companies in DKI Jakarta. The results showed that Quality Management effect Business Sustainability. However, Quality Management has a positive and significant effect on company performance. Ethical leadership has a positive and significant effect on company performance. Ethical leadership also has a positive and significant effect on Business sustainability. Company Performance positively and significantly affects the sustainability of the Umrah travel business in DKI Jakarta. This study encourages company leaders to use a Quality management practice framework to improve company performance and long-term business sustainability. Umrah travel companies must improve the quality of Management practices and long-term business sustainability. In achieving long-term business sustainability, ethical leadership practices and company performance are the foundation and driving forces for achieving these goals. The research update is to add a systemic deposit (implementation guarantee) for every departure plan; every Umrah travel must deposit a minimum departure guarantee of 15-25%.